2007
DOI: 10.1089/acm.2007.6175
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Metastatic Malignant Melanoma with Viscum album Extract (Iscador® M)

Abstract: The use of low-dose Iscador as the sole postoperative modality for the adjuvant treatment of metastatic melanoma was extremely effective and very well tolerated in this patient. It achieved complete response and absence of all complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 6 publications
1
17
0
1
Order By: Relevance
“…Polypeptides, including lectins and viscotoxins, are thought responsible for in vitro immune stimulant and tumor inhibition activity. However, the body of published reports suggesting efficacy for the treatment of cancer lacks welldesigned randomized trials and most of these data are only from small, uncontrolled trials and case reports [135][136][137][138][139][140]. A meta-analysis analyzed 11 of these clinical trials carried out before 1994 and showed no benefit from mistletoe [141].…”
Section: Mistletoementioning
confidence: 99%
“…Polypeptides, including lectins and viscotoxins, are thought responsible for in vitro immune stimulant and tumor inhibition activity. However, the body of published reports suggesting efficacy for the treatment of cancer lacks welldesigned randomized trials and most of these data are only from small, uncontrolled trials and case reports [135][136][137][138][139][140]. A meta-analysis analyzed 11 of these clinical trials carried out before 1994 and showed no benefit from mistletoe [141].…”
Section: Mistletoementioning
confidence: 99%
“…The α2,3-sialic acid residue in receptors that are expressed on the surface of cancer cells is closely associated with the malignant phenotype and metastatic potential of many cancer cells [8,40,41]. The mistletoe lectins are known to bind glycoproteins containing the α2,3-sialic acid residue and are widely used to treat melanoma in Europe [42,43]. The α2,3-sialic acid-binding lectin MAL is also used to recognize these carbohydrates in cancer cells [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, disappearance of colon polyps is otherwise uncommon [19]. Remission of malignant tumours a er intratumoural injection of Viscum album extracts has been reported for cutaneous B-cell lymphoma, cutaneous squamous cell carcinoma, and malignant melanoma [6][7][8], but not yet for colon adenomas. e e ect is plausible given the known immune-stimulatory and cytotoxic e ects of Viscum album extract [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomized controlled tiral (RCT) showed survival bene t in advanced pancreatic cancer [5]. Case reports have documented durable tumour regression [6][7][8]. In colorectal cancer, studies have shown bene ts in terms of reduced cancer recurrence, survival in advanced cancer, and perioperative suppression of natural killer cells [9][10][11], but the speci c e ect of Viscum album extract on colon polyps has not been investigated.…”
Section: Introductionmentioning
confidence: 99%